Pendampingan Persiapan Akreditasi Klinik Swasta di Jawa Barat Sesuai Standar Permenkes No. 34 Tahun 2022 - Muhammad Nur Abdillah (Jurnal Masyarakat Indonesia (Jumas), 2024)
This mentoring program for clinic accreditation preparation in West Java aimed to enhance the readiness of three private clinics in undergoing accreditation surveys in accordance with the standards set by the Indonesian Ministry of Health Regulation (Permenkes) No. 34 of 2022. The activities were conducted through a combination of online consultations, in-person visits, and field inspections, focusing on the preparation of accreditation documents and the assessment of clinic services' compliance with the established standards. The partner clinics included one primary outpatient clinic in Sumedang and two clinics in Bandung Regency, including one specialist eye outpatient clinic. The mentoring results indicated that these clinics achieved a high level of readiness, with a minimum of 85% compliance with the accreditation standards. All accreditation documents were completed, and the implementation of standard operating procedures on-site was deemed adequate. The success of this program was supported by the active involvement of responsible parties for each chapter of the accreditation standards, covering resource management, quality improvement and patient safety, and personal service management. Although challenges such as time constraints and technology adaptation were encountered, mitigation efforts through additional training and schedule adjustments allowed all clinics to participate optimally. The evaluation of the program suggested that the methods used were effective in achieving the goals, although further improvements in internal clinic monitoring and evaluation after mentoring are needed. Overall, the program met its objectives and provided significant benefits to the partner clinics in achieving full accreditation, which will enhance the quality and safety of healthcare services they provide.